Use ecological health monitoring method (EHM) to assess water environmental quality at area dismissing of Nhieu Loc - Thi Nghe channel into Sai Gon - Bich Loc, Do Thi; Canh, Doan; Dang, Phan Doan; Luu, Pham Thanh; Tho, Le Van; Minh Trang, Thai Thi (Academia Journal of Biology, 2012)
The results obtained from EHM project showed that the water environmental quality of studied area has been put in the ranks “B” and “C”, it corresponds with the ecological health categories from average to bad level, the worst level was observed right at discharged throat of Nhieu Loc - Thi Nghe channel, where the water of channel has not been treated completely and having been discharged directly into Sai Gon river. The results of the classifying for water environmental quality derived from ecological health ranking method provided the understandable informations of water pollution levels at defined sites and time. It is serves as a basic for the authorities as well as the citizens to understand the water quality sources and what kinds and whether the water safe and suitable for intentional uses. This research was the first contribution to reality and theory in the field of ecological quality supervising resrearch for the Sai Gon river in particular and for other rivers and canals of Ho Chi Minh city in future.